SUN-LB073 Giant Prolactinomas: Recidive (Case Report) - Galesanu, Corina (J Endocr Soc, 2019)
Introduction: Prolactinomas are rare in childhood and adolescence. The signs and symptoms depend on age, sex, and tumor size and prolactin level. Case report: We present a case of 25-year-old patient diagnosed at age 13 with giant prolactinomas. He came to our observation after then neurosurgery was performed for symptoms of tumor expansion. Elements of sella turcica were not recognizable on the pituitary X-Ray. The CT described a large tumour of the pituitary gland. No pituitary insufficiency was observed after surgery but persistent hyperprolactinemia. Dopamine-agonist therapy was required postoperatively. After five years the patient developed normal puberty, reaching a final high=172cm. After seven years of prolactin level control and no IRM signs of recidive under medical therapy, we lost follow-up. After another 12 years, IRM described a 2/1.3/2.5 cm tumor residue with extension in the right cavernous sinus, PRL levels was high. Cabergoline therapy was reinitiated. Discussions: Neurosurgery was performed before endocrinological evaluation but was not curative. Dopamine-agonists were needed postoperatively. As a result of the favorable evolution of the normalization of the PRL and the disappearance of the pituitary tumor under treatment with cabergoline (seven years), after the interruption of the therapy, at a distance the recurrence occurred. In prolactinomas, first-line treatment is represented by dopamine-agonists. Surgery is reserved for patients resistant to medical therapy and those with severe neurological symptoms at diagnosis. Conclusions: In the case of macroprolactinomas, annual follow-up is required at the long term. In the event of recurrence of symptoms, biological or radiological, therapy with dopamine-agonists is required Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.